2005
DOI: 10.1007/s10549-005-6939-z
|View full text |Cite
|
Sign up to set email alerts
|

Nordihydroguaiaretic Acid (NDGA) Inhibits the IGF-1 and c-erbB2/HER2/neu Receptors and Suppresses Growth in Breast Cancer Cells

Abstract: Nordihydroguaiaretic acid (NDGA) is a phenolic compound isolated from the creosote bush Larrea divaricatta that has anti-cancer activities both in vitro and in vivo. We can now attribute certain of these anti-cancer properties in breast cancer cells to the ability of NDGA to directly inhibit the function of two receptor tyrosine kinases (RTKs), the insulin-like growth factor receptor (IGF-1R) and the c-erbB2/HER2/neu (HER2/neu) receptor. In MCF-7 human breast cancer cells, low micromolar concentrations of NDGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 55 publications
1
93
0
Order By: Relevance
“…These results show that ROS may perform essential functions for both the induction of airway inflammation and for the pathogenesis of asthmatic diseases. Previous studies have revealed that NDGA exerts pleiotropic effects capable of influencing a wide variety of cellular processes, including TGF-β-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). However, its anti-inflammatory effects in allergic inflammation have been investigated to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that ROS may perform essential functions for both the induction of airway inflammation and for the pathogenesis of asthmatic diseases. Previous studies have revealed that NDGA exerts pleiotropic effects capable of influencing a wide variety of cellular processes, including TGF-β-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). However, its anti-inflammatory effects in allergic inflammation have been investigated to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, we utilized Nordihydroguaiaretic acid (NDGA), LOXs inhibitor. The results of previous studies have shown that NDGA exerts pleiotropic effects capable of influencing a broad variety of cellular processes, including growth factor-and TNF-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). It can also induce the expression of NOS, regulate calcium channel activity, and inhibit the growth of β-amyloid protofibrils (Ramasamy et al, 1999;Huang et al, 2004;Moss et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lignans may as well act via other non-hormone related mechanisms e.g. by inhibiting angiogenesis, 45 tyrosine kinases via IGF-1 receptor and c-erbB2/HER2/neu mediated pathways, 46 COX-2 expression 47 or DNA topoisomerase II. 48 Ovariectomized athymic mice with MCF-7 cells has limitations as an animal model to determine the effect of hormonally active compounds on postmenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these RTKs helps in reduction of cell growth and drug development. 96 Several reports demonstrate the evidence for overexpression and hyperactivation of the IGF-IR in the early stages of breast cancer. [97][98][99] The negative expression of IGF-IR, using monoclonal antibodies, antisense IGF-IR, catechols, and transfection methods, Figure 3 Receptor-mediated drug delivery to metastatic breast cancer cells.…”
Section: Igf-irmentioning
confidence: 99%